The Patriotic Act and its far-reaching consequences on freedom of expression in the digital space in Zimbabwe - Simiyu, Marystella Auma (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.